Search for Pseudomonas aeruginosa immune-modulatory but non-inducing agents - Jadhav, Gopal P. (2008)
Dysfunctional immunity which is the most common antecedent of immunological diseases is central to the common disorders like rheumatoid arthritis, psoriasis, thyroid disease, type-1 diabetes mellitus, multiple sclerosis and other autoimmune conditions that are leading causes of chronic morbidities and disabilities. The currently employed therapies suffer from serious side effects. For example, steroid therapy, being nonselective is seldom used. Myleotoxicity limits azathioprine while cyclosporine-A (CsA) and FK506 do show myleo-, nephro and neuro-toxicities. Antibody therapies cause immune mediated toxicity. Therefore, the need of developing less toxic and specific immune modulatory agents is a top priority.